ANALISIS FAKTOR RISIKO KEJADIAN HIPERTENSI PADA MASYARAKAT DI PESISIR SUNGAI SIAK KECAMATAN RUMBAI KOTA PEKANBARU - Sapitri, Nelli; ", Suyanto; Butar-butar, Wasinton Ristua (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTHypertension was one of the deases which often caused cardiovascular disorder and the reason from enhance of death number because of cardiovascular disorder that come from hypertension, was to know the hypertension risk factor and do the prevention. In Indonesia, hypertension was serious problem, beside because of the high prevalension, also the disease came from that is fatal like heart disease, stroke, kidney failure and others. Arm of this experiment to get information about the amount of risk factor which adhere or cannot be change and the risk factor which can be change as hypertension risk factor. The experiment was kind of observasional analytic experiment with case control study. Number of respondent is 78 sample, consist of 39 cases and 39 control. Sample collected was using consecutive sampling method. The data was analyzing bivariat and multivariat with regression logistic method, using SPSS program. Experiment result shows that there were 3 risk factor which related to hypertension event that was physical activity (p=0,000; OR=13,47; 95% CI=3,52-51,58), obecity (p=0,002; OR=6,46; 95% CI=1,95-21,47) dan stress (p=0,016; OR=0,196; 95% CI=0,05-0,74).Keywords : Risk Factor, Hypertension.